Retrial queue with two-way communication and collisions - Nazarov, Anatoly A. (Information Technologies and Mathematical Modelling. Queueing Theory and Applications : 21st International Conference, ITMM 2022, Karshi, Uzbekistan, October 25-29, 2022 : revised selected papers)
In this paper, we consider retrial queue with two types of calls: incoming and outgoing. If the server is busy upon arrival, the incoming call provokes collisions. If two incoming calls cause collision, both of them join the orbit. On the other hand, if an outgoing call is in service upon arrival, incoming call preempts outgoing. In this case, the outgoing call is lost